Rapid Increase of Oral Bacteria in Nasopharyngeal Microbiota After Antibiotic Treatment in Children With Invasive Pneumococcal Disease - Henares, Desiree; Rocafort, Muntsa; Brotons, Pedro; de Sevilla, Mariona F.; Mira, Alex; Launes, Cristian; Cabrera-Rubio, Raul; Muñoz-Almagro, Carmen (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction: Antibiotics are commonly prescribed to young children for treating bacterial infections such as Invasive Pneumococcal Disease (IPD) caused by Streptococcus pneumoniae. Despite the obvious benefits of antibiotics, little is known about their possible side-effects on children’s nasopharyngeal microbiota. In other ecological niches, antibiotics have been described to perturb the balanced microbiota with short-term and long-term effects on children’s health. The present study aims to evaluate and compare the nasopharyngeal microbiota of children with IPD and different degree of antibiotic exposure. Methods: We investigated differences in nasopharyngeal microbiota of two groups of children <18 years with IPD: children not exposed to antibiotics before sample collection (n=27) compared to children previously exposed (n=54). Epidemiological/clinical data were collected from subjects and microbiota was characterized by Illumina sequencing of V3-V4 amplicons of 16S rRNA gene. Results: Main epidemiological/clinical factors were similar across groups. Antibiotic-exposed patients were treated during a median of 4 days (IQR:3-6) with at least one beta-lactam (100.0%). Higher bacterial richness and diversity were found in the group exposed to antibiotics. Different streptococcal amplicon sequence variants (ASVs) were differentially abundant across groups: antibiotic use was associated to lower relative abundances of Streptococcus ASV2 and Streptococcus ASV11 (phylogenetically close to S. pneumoniae), and higher relative abundances of Streptococcus ASV3 and Streptococcus ASV12 (phylogenetically close to viridans group streptococci). ASVs assigned to typical bacteria from the oral cavity, including Veillonella, Alloprevotella, Porphyromonas, Granulicatella or Capnocytophaga, were associated to the antibiotic-exposed group. Common nosocomial genera such as Staphylococcus, Acinetobacter and Pseudomonas were also enriched in the group exposed to antibiotics. Conclusion: Our results point towards a reduction of S. pneumoniae abundance on the nasopharynx of children with IPD after antibiotic treatment, and a short-term repopulation of this altered niche by oral and nosocomial bacteria. Future research studies will have to evaluate the clinical implications of these findings and if these populations would benefit from the probiotic/prebiotic administration or even from the improvement on oral hygiene practices frequently neglected among hospitalized children.